Reordering the machinery of participation with young people. (25th January 2022) - Cowan, Hannah; Kühlbrandt, Charlotte; Riazuddin, Hana
Abstract: In this article, we reflect on our ongoing work that attempts to redistribute the agenda‐setting powers of researchers, research funders and the complex of private and public partnerships in the biomedical sciences. Despite calls for diversification, the current landscape is dominated by a traditional medical habitus that prioritises discovery science. This has moral and political consequences. Simultaneously, we have seen a slow rise in top–down infrastructures of public participation in medical science. While we are critical of the resulting machinery of participation, we believe in its premise that knowledge and expertise are everywhere. In our research project—called Utopia Now!—we have been seeking to involve young people in deciding the future of biomedical research. However, this project is itself premised on a number of our own complicities with the power held by universities and research infrastructures. Here, we explore three preliminary tactics through which we attempt to make these complicities politically productive, taking into account the limitations of working as early career researchers. We find that our mediation between young people and researchers across disciplines is not only integral for re‐politicising medical research, but also changes our understanding of knowledge production as a process of reordering, sorting and sharing.